The effect of CEO reputation on company financial distress: Evidence from Pakistan (Global Business Management Review (GBMR), 2022)
The purpose of this study is to explore the influence of CEO Reputation on the Company Financial Distress. The population of the study is all non-financial companies that are listed on the Pakistan stock exchange (PSX). In this research, the final sample size is 285 companies that cover the period of the study from 2006 to 2017. CEO reputation plays important role in predicting financial distress. Based on the upper echelon theory, CEOs can influence in a company decisions making, value creation and financial reporting decisions based on their specific skills, reputation and personal characteristics. Previous studies in the context of Pakistan are lacking to check the association between CEO reputation and company financial distress. This study contributes to the literature and fills this gap. This study also suggest that to explore the link between CEO reputation and financial distress in the emerging market.